Инна Макарова - Кривицкий Ким Ефимович (Мастера советского кино, 1967)
Экземпляры: КХ (20130227) / Инвентарный номер: 432868 / Цена: 0.71 / Сис.шифр: 85.374.3(2)7-8 / Авт.знак: К 82 / ГРНТИ: 18 / ББК: 85.374.3(2)7-8